Andragogical Epistemology and the Lacanian Discourse of the Hysteric: Learning Through Trauma, Trauma Through Learning - Berry, Michael D. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2008)
Harm, this paper proposes, is a viable teaching objective. Presenting an andragogy of post secondary liberal arts education, this paper explores the relationship between critical thinking and subjective harm, arguing that subjective harm is an inevitable outcome of critical thinking practice. The author situates this teaching methodology within the discourse theory of psychoanalyst Jacques Lacan, positioning this critical thinking andragogy specifically within the Discourse of the Hysteric, which interrogates the institutionalized epistemology present in universities. Defining critical thinking as a subjective cognitive technique adjoined to reflexivity and reflective practice, this paper examines and refutes the university principle of primum non nocere (do no harm), arguing that it represents a logical incoherence in university principles. Semantically and conceptually examining the terminologies involved, the author contends that, to the extent that we accept the definition of “harm” found in the Discourse of the University, any teaching practice that valorizes critical thinking inevitably will, and should, be harmful.